CARDIAC SURGERYThe effects of posterior pericardiotomy on pericardial effusion, tamponade, and atrial fibrillation after coronary artery surgery - Kaya, Mehmet; İyigün, Taner; Yazıcı, Pınar; Melek, Yasin; Göde, Safa; Güler, Salih; Karaçalılar, Mehmet; Satılmışoğlu, Muhammet Hulusi; Erek, Ersin (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : Pericardial effusion and atrial fibrillation occur commonly after coronary artery surgery. Aim of the study: A prospective randomized clinical trial was conducted to evaluate the effects of posterior pericardiotomy on the occurrence of pericardial effusion, tamponade, and atrial fibrillation. Material and methods: The study group consisted of 96 patients (77 male and 19 female) at a mean age of 58.1 ± 9.8 years. The patients were randomly assigned to one of three study groups: patients undergoing posterior pericardiotomy (group I, n = 30), controls (group II, n = 33), and patients with additional posterior pericardial drainage tubes (28 mm) who did not undergo posterior pericardiotomy (group III, n = 33). Results : Postoperative hospitalization (p = 0.03; 11.56 ± 10.64) and reoperation due to tamponade (p = 0.019; 12.1%) were significantly higher in group II. Extensive pericardial effusions were detected in one patient on the first postoperative day (group II, n = 1), in one patient on the fifth postoperative day (group III, n = 1), and in one patient on the 30th day after the operation (group III, n = 1). Pericardial effusion exhibited regression in group I on postoperative day 30 (p = 0.028). A higher rate of postoperative atrial fibrillation was noted in group I, but no significant differences were found between the groups with regard to postoperative atrial fibrillation. Conclusions : Patients who did not undergo posterior pericardiotomy or did not receive posterior chest tubes exhibited residual pericardial effusion, required longer hospitalization, and had to be reoperated due to tamponade. Both posterior pericardiotomy and the use of posterior tubes are effective in the early postoperative period.